2019
DOI: 10.1002/elsc.201800127
|View full text |Cite
|
Sign up to set email alerts
|

Co‐utilization of acidified glycerol pretreated‐sugarcane bagasse for microbial oil production by a novel Rhodosporidium strain

Abstract: Acidified glycerol pretreatment is very effective to deconstruct lignocellulosics for producing glucose. Co‐utilization of pretreated biomass and residual glycerol to bioproducts could reduce the costs associated with biomass wash and solvent recovery. In this study, a novel strain Rhodosporidium toruloides RP 15, isolated from sugarcane bagasse, was selected and tested for coconversion of pretreated biomass and residual glycerol to microbial oils. In the screening trails, Rh. toruloides RP 15 demonstrated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Many of the yeast isolates cultured from the bagasse such as Rhodoturola/Rhodosporidium [36,37], Cryptococcus/Papiliotrema laurentii [38] and Meyerozyma caribbica [39] are reported to accumulate high levels of microbial oil. Indeed we demonstrated that the bagassederived strain RP15 (Rhodosporidium toruloides) produced higher yields of intracellular microbial oil when grown on pre-treated bagasse compared to synthetic media and compared to the ATCC type strain [67].…”
Section: Discussionmentioning
confidence: 90%
“…Many of the yeast isolates cultured from the bagasse such as Rhodoturola/Rhodosporidium [36,37], Cryptococcus/Papiliotrema laurentii [38] and Meyerozyma caribbica [39] are reported to accumulate high levels of microbial oil. Indeed we demonstrated that the bagassederived strain RP15 (Rhodosporidium toruloides) produced higher yields of intracellular microbial oil when grown on pre-treated bagasse compared to synthetic media and compared to the ATCC type strain [67].…”
Section: Discussionmentioning
confidence: 90%
“…In addition, many microorganisms can use glycerol as a carbon source for biofuel and biochemical production. 12 Glycerol pretreatment can be undertaken as a stand-alone process or in combination with acidic/alkaline catalysts. 9,11 Acid-catalyzed glycerol (AG) pretreatment is more attractive because to achieve high glucan digestibility it requires shorter reaction times (15−30 min) and lower temperatures (130−170 °C) compared with stand-alone and alkaline-catalyzed pretreatments (190−220 °C and 15−240 min).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Various organosolv pretreatments have been developed using alcohols (ethanol, methanol, butanol, and butanediol), organic acids (acetic acid and formic acid), ketones (acetone and methyl isobutyl ketone), furans (tetrahydrofuran and methyl tetrahydrofuran), lactones (γ-valerolactone), and polyols (ethylene glycol, propanediol, and glycerol) to fractionate lignocellulosic biomass into its individual components. Among them, glycerol pretreatment is attractive because glycerol is a low-cost, nontoxic, nonflammable solvent, which is widely available as a by-product of the biodiesel industry. , In addition, any residual glycerol remaining in the biomass after pretreatment is less inhibitory to enzymatic hydrolysis and fermentation compared with other solvents. In addition, many microorganisms can use glycerol as a carbon source for biofuel and biochemical production . Glycerol pretreatment can be undertaken as a stand-alone process or in combination with acidic/alkaline catalysts. , Acid-catalyzed glycerol (AG) pretreatment is more attractive because to achieve high glucan digestibility it requires shorter reaction times (15–30 min) and lower temperatures (130–170 °C) compared with stand-alone and alkaline-catalyzed pretreatments (190–220 °C and 15–240 min). , …”
Section: Introductionmentioning
confidence: 99%
“…6 ). Previously, we reported that the addition of yeast extract (10 g/L) and peptone (20 g/L) (YP) accelerated fermentation, particularly during glycerol conversion [ 28 ]. Additionally, nonenzymatic proteins such as corn steep liquor, yeast extract, and peptone have enhanced rice straw enzymatic hydrolysis by 12.7%, 13.5%, and 13.7%, respectively [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glycerol has received considerable attention as a cost-effective material for the biorefinery of lignocelluloses, such as sugarcane, softwood, and hardwood, during pretreatment with and without acid catalysts including AlK(SO 4 ) 2 (alum) and other Lewis acids using conventional and microwave heating [ 3 , 26 – 29 ]. After pretreatment, glycerol was used as a carbon source to produce microbial oils in previous studies [ 28 , 29 ]. Recently, we developed an efficient glycerol-converting yeast strain by genetically modifying the oxidation of cytosolic NADH through an O 2 -dependent dynamic shuttle and abolishing both glycerol phosphorylation and biosynthesis in Saccharomyces cerevisiae as well as by the vigorous expression of whole genes in the dihydroxyacetone pathway [ 30 ].…”
Section: Introductionmentioning
confidence: 99%